See & Eat! Using E-books to Promote Vegetable Eating Among Preschoolers: Findings From an Italian Sample - Caputi, Marcella; Dulay, Katrina May; Bulgarelli, Daniela; Houston-Price, Carmel; Cerrato, Giuseppina; Fanelli, Mauro; Masento, Natalie A.; Molina, Paola (Frontiers in Psychology, 2021)
Different strategies have been developed to help parents with introducing new or disliked vegetables. Nonetheless, many parents of preschoolers struggle against children’s refusal to eat vegetables. In this study, we aimed to evaluate the effectiveness of e-books in promoting positive attitudes towards vegetables through repeated visual exposures. A total of 61 families with preschoolers joined the See & Eat study and received an e-book about one of two vegetables chosen from a list of 24. Parents provided ratings of children’s willingness to taste, intake, and liking of the chosen vegetables before and after reading the e-book; parents also evaluated their children’s food fussiness and their agreement with respect to three mealtime goals of the family. Using a 2 (vegetable: target or non-target) × 2 (time: pre-test or post-test) within-subjects analysis, results from 53 families revealed a significant increase in children’s willingness to taste, intake, and liking at post-test of both target and non-target vegetables. Following a two-week parent-child e-book reading intervention, children’s food fussiness and parents’ endorsement of positive mealtime goals slightly but significantly increased. Results suggest that e-books are effective in encouraging healthy eating among preschoolers and that the positive effect of e-book reading can generalize to other vegetables.